Traces of past bog burning culture in rewetted bog soils (Emsland Region, Germany) - Nachtigall, Solveig; Stockenhofen, Thomas; Giani, Luise (ERDKUNDE, 2023)
Until the beginning of the 20th century, bog burning culture was a common cultivation system for food production on otherwise non-arable bog peat soils. Burning and preliminary drainage of the peat impacted the soils nutrient supply, bog morphology and soils properties. To gain insights into the long-term effects of bog burning culture on the landscape and soils, a burned and unburned area within a rewetted bog complex were comparatively analysed. It was hypothesised that bog burning had a lasting effect on the soil chemistry, that the trenches created for drainage prior to burning are still detectable in the bog morphology, and that the altered soil chemistry exhibiting enhanced nutrient supply resulted in a change of vegetation patterns. To verify this, the soil chemistry was analysed regarding pH, carbon/nitrogen (C/N) ratio, and contents of plant available phosphate (PO43-) and potassium (K). The morphology was examined by means of aerial imagery and vegetation patterns were assessed in the field. It was shown that while PO43– contents were similar, pH values and K contents of the burned area were elevated compared with the unburned area. Accordingly, they can be used as an indicator for bog burning culture, even a century after the end of the practice. As expected, C/N ratios were narrowed in the burned area, which however cannot exclusively be attributed to bog burning, since peat mineralisation in the previously drained bog soils caused narrowing C/N ratios as well. The trench structure for drainage was still visible in aerial images and vegetation patterns were similar in the burned and unburned areas. Overall, the aftermath of bog burning was still apparent in morphology and soil chemistry, however the effect was less severe than expected, as vegetation patterns and the overall restoration success were not impacted. This provides a reasonable expectation that bogs are resilient towards bog burning and the latter is no obstacle for successful restoration.